Associations between individual-level characteristics and exposure to physically violent behavior among young people experiencing homelessness: A meta-analysis. (July 2019) - Heerde, Jessica A.; Hemphill, Sheryl A.
Abstract: Risk factor reduction approaches may decrease exposure to violence among young people experiencing homelessness. This study presents a meta-analysis exploring associations between characteristics of young people experiencing homelessness (individual-level factors) and exposure to physically violent behavior, both as perpetrators and as victims. A series of meta-analyses using random effects models were conducted, examining 426 effect sizes, calculated from findings across 26 studies. Data were analyzed from 8842 homeless young people, aged 13–26 years from North America. Individual-level factors were significantly associated with both perpetration of physically violent behavior (OR 4.87, p < .0001) and physical violence victimization (OR 4.15, p < .0001). Homelessness experiences (e.g. length of time homeless) were associated with both perpetration of, and victimization from, physically violent behaviors. Perpetration of physically violent behavior was associated with physical violence victimization (OR 11.90, p < .0001). Prevention and intervention approaches seeking to address exposure to violence, both as perpetrators and as victims, can be informed by future research investigating risk factor reduction approaches. Highlights: Risk factor reduction approaches may decrease exposure to violence among homeless young people. Individual-level factors are associated with exposure to violence. Few studies have examined the role of protective factors for exposure to violence. Reciprocal associations between violence perpetration and victimization require investigation. Prevention strategies for addressing exposure to violence can be informed by risk factor reduction approaches.